Mirabegron and antimuscarinics for treating ureteral stent-related symptoms: a systematic review and meta-analysis of RCTs - Youyi Lu; Qi Li; Qingsong Zou; Yuanshan Cui (Frontiers Media S.A., 2023)
Objective: We conducted a meta-analysis to assess the efficacy and safety of mirabegron (50 mg/day) and antimuscarinics in treating ureteral stent-related symptoms (SRSs).Methods: All randomized controlled trials (RCTs) were identified by searching PubMed, Embase, Web of Science, and Cochrane Library. The RevMan version 5.3.0 software was used for statistical analysis.Results: This meta-analysis included five RCTs involving 317 patients. A fixed effects model revealed that mirabegron was superior to antimuscarinics in treating urinary symptoms (MD −1.39, 95% CI −2.63 to −0.15, p = 0.03) and general health (MD −1.65, 95% CI −2.60 to −0.69, p = 0.0007) 1 week after treatment initiation. We observed no significant differences in body pain (MD 0.05, 95% CI −1.06 to 1.15, p = 0.94), work performance (MD −0.86, 95% CI −1.77 to 0.06, p = 0.07), and sexual matters (MD 0.03, 95% CI −0.77 to 0.83, p = 0.94). Two weeks after treatment initiation, the ureteral stent symptom questionnaire (USSQ) revealed no significant differences between the two groups. The mirabegron group demonstrated a significant improvement in the quality of life (QoL) (MD −0.18, 95% CI −0.34 to −0.01, p = 0.03), while the International Prostate Symptom Score did not reveal a significant difference between the two groups (MD −0.74, 95% CI −1.79 to 0.32, p = 0.17). Regarding safety, a pooled data analysis presented that the incidence of constipation was lower in the mirabegron group (OR 0.10, 95% CI 0.01 to 0.77, p = 0.03). The mirabegron and antimuscarinics groups did not differ significantly concerning the risk of dry mouth (OR 0.15, 95% CI 0.02 to 1.27, p = 0.08).Conclusion: Mirabegron is superior to antimuscarinics in alleviating ureteral SRSs and improving QoL. Additionally, mirabegron 50 mg/day presented safety with a lower incidence of constipation.